(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays Information Technology (It) Has Helped The Industries To Deal With The Challenges When New Economy Poses. Moreover, Institutions Rely On It Gathering, Processing, Analysing, And Providing Information And Services In Order To Meet The Customers’ Need. The Analysis And Processing Of Information In Organizations In General And Enterprises In Particular Need To Be Accurate And Timely To Support Decision-Making As Well As Management And Planning Of The Management Board. The Operation And Use Of Information Systems (Is) To Replace The Traditional Information Management Methods In Many Businesses Is No Longer A New Thing. Digitalization Of Products And Services Is A Fast-Moving, Global Megatrend That Is Fundamentally Changing Existing Value Chains Across Industries And Public Sectors. Modern Wireless Internet-Based Technologies With Real-Time Data Analysis Are The Common Tools Of Digital Applications To Provide Organizations With Great Business Improvements. The Topic “Enhancing Operational Efficiency Of Information Technology Systems: The Experience Of Saigon Union Company, Vietnam” Is Conducted To Evaluate The Factors Affecting The Improvement Of The Operational Efficiency Of It Systems For Saigon Union, Vietnam. The Target Of Is/It System Is Always Closely Linked With The Goals Of The Business. It Can Be Said That The Is/It System Is An Effective Tool Create Brand Value And Optimal Competitive Position In The Market Not Only In Vietnam But Also In International Markets. Especially During The Covid-19 Epidemic, Enhancing Operational Efficiency Of It System Is One Of The Effective Solutions To Enhance The Competitiveness Of Saigon Union.